Nerve Conduction Study in Early Diagnosed Cases of Hypothyroidism in Central India - Komal Meshram1, Alka Rawekar2, Ajay Meshram3, Harshwardhan Meshram4, Anjali Vaggha5, Shilpa Ingle6 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Thyroid gland has multiple effects on the neuromuscular system and brain, its dysfunction is associated withcharacteristic symptoms and signs with functional alterations in many organs and systems. Thyroid diseasemay cause signs and symptoms of neuromuscular dysfunction. Hypothyroidism has been associated with theclinical features of proximal muscle weakness, mononeuropathy and sensorimotor polyneuropathy.Nerveconduction studies (NCS) are useful adjunct to the clinical examination of the peripheral nervous systemas it is helpful to test speed of signals through a nerve. They help to delineate the extent and distribution ofthe neural lesion and distinguish two major categories of peripheral nerve disease demyelination and axonaldegeneration. Present cross sectional studywas conducted at Central Neurophysiology Laboratory in tertiarycare teaching hospital, J.N.M.C, Sawangi (M), Wardha catering to rural population of central India to assessthe nerve conduction in early diagnosed hypothyroid patients. Total twenty seven patients; 20-50yrs of agewere screened for nerve conduction.In our study we got mixed type of peripheral neuropathy. Out of 27patients with age 18-30 yrs- 1(16.67%), 31-40 yrs- 13(61.90%) and 41-50 yrs -7 (33.3 %) had abnormalNCS. Occurrence of neuropathy was more common in female patients 80.95% as compared to male patients19.05%.Sensory nerve action potential (SNAP) amplitudes and conduction velocity were significantlyreduced (p<0.05) in cases diagnosed as hypothyroidism in median (77%), sural (70%) and ulnar nerves(33%)as compared to controls.